(untitled) (Scientific journal of the Fergana State University, 2025)
This article is focused on studying ectoparasites in fish populations in the Fergana Valley’s water bodies and their ecological and economic significance. The negative impact of ectoparasites on fish, including their growth rate, reproductive activity, and survival rate, is highlighted. The ecological conditions of the water, particularly temperature, oxygen content, and organic matter levels, directly influence the development and spread of parasites. The study emphasizes the negative effect of parasites on fish populations, especially by increasing the risk of disease and potentially causing economic losses to the fishing industry. To effectively combat ectoparasites, the article stresses the need to apply ecological and biological methods and improve the quality of the fish’s living environment. This article serves as a scientific basis for developing scientific approaches to combating ectoparasites in the Fergana Valley’s fishing industry and ensuring the health of fish populations.